Effect of performance based financing home visiting on the use of modern methods of contraception in the kumbo east health district, Cameroon. Issue 1 (December 2016) - Egbe, Thomas; Atashili, Julius; Talla, Emmanuella; Atanga, Mary
Abstract Background The use of modern methods of contraception (MMC) as defined by the World Health Organization still remains a challenge in most of Sub-Saharan Africa. Performance Based Financing (PBF) home visit was introduced in 2012 to increase the use of those modern methods in the Kumbo East Health District (KEHD), Cameroon. We determined the utilization rates of MMC in areas in the KEHD with PBF home visits compared with those areas with no home visits. Methods This was a cross sectional study carried out in the KEHD during the period February 1 to May 31, 2015. A multistage cluster sampling method was used to recruit 262 and 221 women aged 15–49 years in the intervention and nonintervention health areas, respectively. A structured, closed ended questionnaire was used. Results The average age of women was similar in both groups 30.40 (SD 8.57); median 30 years in the intervention group and 30.49 (SD 7.84); median 30 years in controls. Most participants in the intervention health area (60.3 %) used modern methods of contraception compared to 46.6 % of those in the control group (aOR: 1.75 %; 95 % CI: 1.212.53) and the most commonly used MMC was medroxyprogesterone in the intervention group and condoms in the control area. Conclusion Utilization of MMC was significantly higher in the area with PBF home visits than in areas without that service. While this indicates that the intervention has benefit, there may be other contributing factors.